A new experimentally validated formula to calculate the QT interval in the presence of left bundle branch block holds true in the clinical setting. Issue 2 (26th August 2016) - Bogossian, Harilaos; Frommeyer, Gerrit; Ninios, Ilias; Pechlivanidou, Eleni; Hasan, Fuad; Nguyen, Quy Suu; Mijic, Dejan; Kloppe, Axel; Karosiene, Zana; Margkarian, Artak; Bandorski, Dirk; Schultes, Dominik; et al.
Abstract : Background: The evaluation of the QT interval in the presence of left bundle branch block (LBBB) is associated with the challenge to discriminate native QT interval from the prolongation due to the increase in QRS duration. The newest formula to evaluate QT interval in the presence of LBBB suggests: modified QT during LBBB = measured QT interval minus 50% of LBBB duration. The purpose of this study is therefore to validate the abovementioned formula in the clinical setting. Methods: Validation in two separate groups of patients: Patients who alternated between narrow QRS and intermittent LBBB and patients with narrow QRS who developed LBBB after transcatheter aortic valve implantation (TAVI). Results: The acquired mean native QTc intervals and those calculated by the presented formula displayed no significant differences ( p > .99 and p > .75). Conclusions: In this study we proved for the first time the validity and applicability of the experimentally acquired formula for the evaluation of the QT interval in the presence of LBBB in a clinical setting.